دراسة تطبيقية في شركة التأمين العراقية العامة: study in the "General Iraqi Insurance Company" (Journal of Accounting and Financial Studies ( JAFS ), 2014)
The life insurance marketing faces many difficulties because it is not a current tangible commodity, so it needs a planning for promotional activities and data about prospective applicants according to many factors such as age and residence area ​​, marital status and profession to determine the group wich need insurance covers.                                                                                                   In this research, we are trying to study the impact of the professions as a factor in underwriting and the demand for insurance and to suggest practical proposals to examine the insurable applications and identify its classifications.